Comparison of helical tomotherapy treatment plan verification using ionization chamber, film and two-dimensional ionization chamber array - Lekkong, Issara; Wanwilairat, Somsak; Tharavichitkul, Ekkasit (Biomedical Sciences and Clinical Medicine, 2016)
Objective To evaluate the performance of ionization chamber, film and two-dimensional ionization chamber array used for the helical tomotherapy treatment plans verification. Methods The treatment plan of thirteen patients who were treated on Helical Tomotherapy in Division of Therapeutic Radiology and Oncology, Faculty of Medicine, Chiang Mai University were used to verify in this study. The verification point dose were measured by an ionization chamber and Octavius 2D array. The dose distribution were measured by film and Octavius 2D array. The point dose and dose distribution were compared using the percentage dose difference and gamma index passing rate, respectively. Results The treatment plan verification based on absorbed point dose measurement using ionization chamber and Octavius 2D array demonstrated the root mean square of the percentage dose difference obtained from measured values in comparison to calculation were 0.38 and 0.84 for ionization chamber and Octavius 2D array, respectively. For the relative dose distribution, the average of the percentage gamma index passing rate with 3% /3mm and the standard deviation of the film and Octavius were 86.59±11.81 and 96.39±6.79, respectively. Conclusion The point absorbed and relative doses verification by ionization chamber, film and Cheese phantom with a standard method are accurate and effective. The point absorbed and relative doses verification by Octavius detector and Octavius phantom are accurate and effective for the helical tomotherapy treatment plan.